Stakeholder management and social responsibility concepts, approaches and tools in the Covid context - Nicolescu, Ovidiu (Routledge advances in management and business studies, 2022)
"The main objective of this book is to provide an innovative set of concepts and tools regarding company management, internal and external stakeholders and social responsibilities, reflecting the necessities and opportunities generated by the digital transformation, the transition to a knowledge-based economy and the Covid-19 crisis. The book, based on a holistic vision and contextual approach of business, contributes to the development of company management and stakeholder and social responsibility theories and practices, being structured in twelve chapters. The original company management vision, approaches and tools are based on three pillars: a new 'manager-relevant stakeholder' rather than 'manager-subordinate' managerial paradigm; a new type of company social responsibility rather than corporate social responsibility; and a new concept of company-relevant stakeholder rather than that of salient stakeholders. The book contains two innovative managerial mechanisms: the managerial synapse and company-relevant stakeholders-based management system able to help companies and stakeholders face successfully the challenges of digital transformation and the Covid-19 crisis and to generate greater organization functionality and performance. The book will be of interest to company managers and management specialists, management academics, consultants and researchers and MBA students interested in a style of management with social responsibility at the forefront"--